A case of lymphoplasmacytic lymphoma mimicking as chronic lymphocytic leukemia - Manoharan, Elamathi; Ramalingam, Thulasi Raman (International Journal of Research in Medical Sciences, 2023)
Lymphoplasmacytic lymphoma (LPL) is a B-cell non-Hodgkins lymphoma (B-NHL) that has small lymphocytes, plasmacytoid lymphocytes and plasma cells in varying proportions. It commonly involves the bone marrow, lymph nodes, spleen and rarely other extra-medullary sites. LPL tends to have a varied morphology and immunophenotype (IPT). Though it is characterized by the presence of monoclonal IgM protein in serum, it can also be seen in other B-NHL. Thus, it may impose a diagnostic challenge by morphology and IPT in some cases. Chronic lymphocytic leukaemia (CLL) is another small B cell NHL, which has a more typical morphology and characteristic IPT. IPT is done by flow cytometry (FCM), which is a rapid and efficient tool in the diagnosis of NHL involving blood and marrow. We present a case of LPL which mimicked CLL by morphology and IPT.